2016
DOI: 10.1371/journal.pone.0157534
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Nucleolin Affects Microtubule Dynamics

Abstract: Nucleolin is present in diverse cellular compartments and is involved in a variety of cellular processes from nucleolar structure and function to intracellular trafficking, cell adhesion and migration. Recently, nucleolin has been localized at the mature centriole where it is involved in microtubule nucleation and anchoring. Although this new function of nucleolin linked to microtubule regulation has been identified, the global effects of nucleolin on microtubule dynamics have not been addressed yet. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Interestingly, each of these reports also found a significant number of nucleolar and ribosomal proteins associated with the mitotic spindle, suggesting a link between the nucleolus, RNA and MT dynamics. Several of these factors have been further shown to regulate MT dynamics, including nucleolin, NPM1 and RPS3 ( 37 , 55 , 56 ). Thus, we hypothesized that FKBP25 could play a similar role in the regulation of MT dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, each of these reports also found a significant number of nucleolar and ribosomal proteins associated with the mitotic spindle, suggesting a link between the nucleolus, RNA and MT dynamics. Several of these factors have been further shown to regulate MT dynamics, including nucleolin, NPM1 and RPS3 ( 37 , 55 , 56 ). Thus, we hypothesized that FKBP25 could play a similar role in the regulation of MT dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these observations establish FKBP25 as a bridge between RNA and the cytoskeleton that should be further investigated. The precedent for such a connection is already established from reports of ribosomal proteins, NPM and NCL associating with MTs ( 37 , 55 , 56 ). Notably, these are also FKBP25 interactors ( 31 , 50 ).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, an accumulation of immature centrosomal structures is observed which is accompanied with multipolar centrosomal structures. Recent work also described a function of NCL in microtubule anchorage at centrosome and in microtubules dynamics 28 , 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, cell shape is drastically affected when NCL expression is reduced 27 29 . Many studies have shown that the expression of NCL is required for cell migration or adhesion 34 37 .…”
Section: Resultsmentioning
confidence: 99%